Pengaruh Akuntansi Lingkungan dan Tanggung Jawab Sosial Terhadap Kinerja Keuangan Perusahaan - Tsaniyah, Salsabila; Hidayati, Wahyu Nurul (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of environmental accounting and social responsibility on corporate financial performance in Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange in 2020-2024. The sample selection technique used purposive sampling and data processing using E-views 12 as a test tool. The population in this study were Consumer Non- Cyclicals companies listed on the Indonesia Stock Exchange in 2020-2024, totaling 125 companies. The sample of this study amounted to 12 companies. This type of research is research with a quantitative approach. The analysis method used is panel data regression analysis. The results of the study simultaneously show that environmental accounting and social responsibility had significant effect on the company's financial performance, while environmental accounting had significant effect on the company's financial performance, and social responsibility did not have any significant effect on the company's financial performance in increasing company value in the consumer non-cyclicals sector.